Pengaruh Politik Multikultural pada Jabatan Struktural Pemerintahan di Kabupaten Nias Utara - Adrian Dirgaputra Zebua; M. Arif Nasution; Marlon Sihombing (PERSPEKTIF, 2022)
This research is about analyzing the political influence of multiculturalism in the structure of the newly elected government, namely Amizaro Waruwu who is the current Regent in North Nias. This study uses Will Kymlica's multicultural political theory which is used to analyze minority rights in politics and can occupy the structure of government positions in North Nias Regency. Agnes Heller's theory of identity politics is used to conclude how the identity of the regional head is one of the considerations in determining the structural positions of the executive government in North Nias Regency.          This research method uses qualitative methods with descriptive data analysis techniques to answer one or several questions regarding the state of the object or subject in detail. Data collection techniques were carried out by interview methods and literature study. In this research, we see and provide understanding of two things. First, the decentralization system gives rise to a pattern of recruitment of SKPD leaders in determining the government structure that prioritizes the majority community to take office. Second, with the decentralization system, the community will be more active in determining every government policy and being directly involved in every political process in North Nias Regency.Keywords: Multicultural, Government, Recruitment Pattern.